Analisis Framing pada Pemberitaan Tewasnya Osama bin Laden di Harian Republika-Kompas - Armiah Najla; syamsul Rijal; nur falikhah (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Mass media have a strong influence in creating the image of characters. The actions and behavior of Osama (Usama) as the leader of al Qaeda  also not immune from the attention of the media. When he was killed by the military elite of Obama, the events are the news headlines in a number of international and national media. Two major newspapers in Indonesia also took a moment to compose how media policy is. Through study groups, the authors traced the creation of the meaning behind the choices of topics taken by two media sources through its affiliates.  Republika chooses  headlines representing subjectivity Islamic-leaning newspaper, giving sympathy and empathy on the issue of Islamic societies in the middle east, whereas Kompas prefers describing the greatness and success of the United States crippled Osama, while putting out the issue to the world's terrorists locality Indonesia.